Autism spectrum disorders: Neuroimaging findings from systematic reviews. (February 2017) - Pua, Emmanuel Peng Kiat; Bowden, Stephen C.; Seal, Marc L.
Highlights: Neuroimaging findings in Autism Spectrum Disorders (ASD) are heterogeneous and definitive neural correlates in ASD have yet to be identified. Despite the utility of systematic reviews, findings from multiple independent neuroimaging meta-analyses in ASD appear discrepant. Key issues contributing to inconsistent results in ASD research are discussed. Putative findings in ASD research should be re-examined in light of new advances in neuroimaging research methods. Abstract: Autism Spectrum Disorders (ASD) are a cluster of neurodevelopmental conditions associated with core deficits in social communication, social interaction, and restricted and repetitive behaviours. Current evidence suggests a complex interaction between genetic and environmental factors that underlie the heterogeneity of neuroanatomy and clinical symptomatology of ASD across a spectrum. Although abnormalities in brain structure and function have been implicated in the neurodevelopmental trajectory of ASD, the search for definitive neuroimaging markers remains obscured by inconsistent or incompatible findings. Specifically, discrepancies between independent studies impede reliable identification of the nature and form of atypical alterations in grey-matter structural morphometry and intrinsic functional networks in ASD. This review aims to illustrate the heterogeneity in ASD neuroimaging literature by comparing systematic reviews and meta -analyses of neuroimaging investigations in ASD over the last several decades, with particular emphasis on structural morphometry, structural connectivity and resting-state intrinsic connectivity techniques. Given the unique challenges in ASD research, standardized methodologies to validate potential neuroimaging markers will be an important step towards advancing clinical and research methods to investigate complex aetiological mechanisms and risk factors underlying ASD.